Clinical characteristics and long-term mortality of patients with midrange ejection fraction undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction. (25th November 2020) - Vratonjic, J; Milasinovic, D; Asanin, M; Vukcevic, V; Zaharijev, S; Pavlovic, A; Jelic, D; Radomirovic, M; Zobenica, V; Mehmedbegovic, Z; Stankovic, G
Abstract: Background: Previous studies associated midrange ejection fraction (mrEF) with impaired prognosis in patients with ST-elevation myocardial infarction (STEMI). Purpose: Our aim was to assess clinical profile and short- and long-term mortality of patients with mrEF after STEMI treated with primary percutaneous coronary intervention (PCI). Methods: This analysis included 8148 patients admitted for primary PCI during 2009–2019, from a high-volume tertiary center, for whom echocardiographic parameters obtained during index hospitalization were available. Midrange EF was defined as 40–49%. Adjusted Cox regression models were used to assess 30-day and 5-year mortality hazard of mrEF, with the reference category being preserved EF (>50%). Results: mrEF was present in 29.8% (n=2 427), whereas low ejection fraction (EF<40%) was documented in 24.7% of patients (n=2 016). mrEF was associated with a higher baseline risk as compared with preserved EF patients, but lower when compared with EF<40%, in terms of prior MI (14.5% in mrEF vs. 9.9% in preserved EF vs. 24.2% in low EF, p<0.001), history of diabetes (26.5% vs. 21.2% vs. 30.0%, p<0.001), presence of Killip 2–4 on admission (15.7% vs. 6.9% vs. 26.5%, p<0.001) and median age (61 vs. 59 vs. 64 years, p<0.001). At 30 days, mortality was comparable in mrEF vs. preserved EF group, while it was significantly higher in the low EF group (2.7% vs. 1.6% vs. 9.4%, respectively, p<0.001). At 5 years, mrEF patients had higher crude mortality rate as compared with preserved EF, but lower in comparison with low EF (25.1% vs. 17.0% vs. 48.7%, p<0.001) (Figure). After adjusting for the observed baseline differences mrEF was independently associated with increased mortality at 5 years (HR 1.283, 95% CI: 1.093–1.505, p=0.002), but not at 30 days (HR 1.444, 95% CI: 0.961–2.171, p<0.001). Conclusion: Patients with mrEF after primary PCI for STEMI have a distinct baseline clinical risk profile, as compared with patients with reduced (<40%) and preserved (≥50%) EF. Importantly, mrEF did not have a significant impact on short-term mortality following STEMI, but it did independently predict the risk of 5-year mortality. Funding Acknowledgement: Type of funding source: None